'To receive guests with kindness': Symbols of Hospitality, Nobility and Diplomacy in Alexander Seton's Designed Landscape at Fyvie Castle. Issue 1 (November 2015) - Fraser, Shannon Marguerite
Abstract : An ongoing programme of research into the nature of the late sixteenth-/early seventeenth-century designed landscape around Fyvie Castle, Aberdeenshire is beginning to reveal the grand vision of its creator Alexander Seton, Lord Fyvie. This paper seeks to explore some of the symbolic narratives Seton embedded within the formal landscape he designed at Fyvie in the years around 1600, which was ultimately swept away by a Picturesque impetus in the late eighteenth century.